Rightward Tympanic Membrane Temperature Bias During Acute Restraint-Isolation Stress in Marmoset Monkeys - Pereira, Lucas C.; Maior, Rafael S.; Barros, Marilia (Frontiers in Neuroscience, 2019)
Restraint is widely used to experimentally assess stress-induced effects. Surprisingly, little is known on how marmosets – an increasingly used small primate – process and respond to restraint stress. Here we assessed blood cortisol concentration and tympanic membrane temperatures (TMT) in adult marmoset monkeys (Callithrix penicillata) during 0, 15 or 30 min of restraint and social isolation in a small cage. TMT reflects blood flow to the cerebral hemispheres, which in turn reflects neural activity. Baseline tympanic membrane temperatures (TMT) were subtracted from post-test measures to establish shifts in blood flow possibly induced by ipsilateral brain activity. Cortisol was assayed immediately after the post-test assessment of the TMT. Marmosets restrained-isolated for 15 or 30 min had higher cortisol levels than the non-restrained-isolated group. Furthermore, significant changes in TMT were detected only in the right ear of the restrained-isolated groups, this effect being unrelated to overall body temperature or the time needed to capture/measure the TMT. Adult marmosets thus readily perceive a significant reduction in their range of movement – even if brief and in social isolation – as an event of sufficient negative intensity and/or duration to activate a pertinent neuroendocrine response. Also, an asymmetrical shift in their TMT reflects that such an aversive event may be rightwardly biased in this primate.